Development of Short Tutorial Video Learning Media Instagram in the Motorcycle Chassis Maintenance Courses at Vocational High Schools - Waruwu, Buala Jefriana; Jalinus, Nizwardi; Wulansari, Rizky Ema; Purwanto, Wawan (The Indonesian Journal of Computer Science, 2023)
This study uses a Research and Development (R&D) design, with the ASSURE development model. ASSURE development procedures, namely Analyze learner characteristics, State Standards and Objectives, Select Strategies, Technology, Media, and Materials, utilize media and materials, require learner participation, evaluate and revise. The data analysis technique used describes the validity, practicality, and effectiveness of the developed media. The product results obtained from this development research are video tutorial learning media. Based on the results of this study it was concluded that the developed media was declared "valid" by media experts with an average value of 0.77, and also declared "valid" by material experts with an average value of 0.85. The media developed was declared "practical" with a practicality value from the teacher's response with a result of 96.41% and a student response of 88.10%, and the video tutorials produced were effectively used with the results of a comparison of pretest and posttest learning outcomes seen from students' classical completeness of 100% and a gain score of 0.61 in the medium category. From the results of the research conducted, it can be concluded that short video tutorial learning media via Instagram are valid, practical and effective in the subject of maintaining motorcycle chassis in vocational high schools.